Prevalence of ESBL resistance genes and fecal carriage of multidrug-resistant Pseudomonas aeruginosa isolates from patients with chronic kidney disease at the Laquintinie Hospital in Douala, Littoral Region, Cameroon - Ballue S.T. Dadjo; Armelle T. Mbaveng; Michael F. Kengne; Ornella D. Tsobeng; Giresse D.T. Fonjou; Victor Kuete (Journal of Infection and Public Health)
Background: Pseudomonas aeruginosa is an opportunistic Gram-negative bacterium capable of causing severe infections in immunocompromised patients such as those suffering from chronic kidney disease (CKD). This study aimed to determine the resistance profile of Pseudomonas aeruginosa, and the prevalence of extended-spectrum β-lactamase (ESBL) resistance genes in patients with chronic kidney disease. Methods: The prevalence of Pseudomonas aeruginosa was investigated in 458 patients, including 197 CKD patients and 261 patients suffering from gastrointestinal infections. The study was conducted at Laquintinie Hospital in Douala from January 2022 to December 2023. Stool samples were used to isolate Pseudomonas aeruginosa on Cetrimide agar. Antibiotic susceptibility testing was carried out using the Kirby-Bauer diffusion method. extended-spectrum β-lactamase (ESBL) resistance genes were detected by the polymerase chain reaction (PCR) method. Results: The prevalence of fecal carriage of Pseudomonas aeruginosa was 9.17 % (n = 42/458), including twenty-nine (69.05 %) in patients with chronic kidney disease and thirteen (30.95 %) in patients without chronic kidney disease. The Pseudomonas aeruginosa isolates had a high rate of resistance to ceftazidime (72.41 %) in patients with CKD compared to patients without CKD (69.23 %). All isolates had a high resistance to ticarcillin (93.10 % and 92.31 %). The prevalence of multidrug-resistant (MDR) Pseudomonas aeruginosa isolates was 73.81 %. The MDR Pseudomonas aeruginosa were higher (70.97 % vs. 29.03 %) in patients suffering from CKD compared to patients without CKD. Up to 85.71 % of the Pseudomonas aeruginosa isolates harbored at least one ESBL gene. The blaTEM type gene (66.67 %) was the most frequently detected gene, followed by blaCTX-M (61.90 %) and blaSHV (47.62 %). ESBL resistance genes were more common in CKD patients (72.22 %) compared to patients without CKD (27.78 %). Conclusion: These results demonstrate that antibiotics belonging to the carbapenem and aminoglycoside classes could be used for Pseudomonas aeruginosa infection. This highlights the importance of regular surveillance of multidrug resistance and extended-spectrum β-lactamase production for Pseudomonas aeruginosa infections in patients with chronic kidney disease.